Optimalisasi Pengobatan Tekanan Darah dengan Fixed-Dose Combination Perindopril/Amlodipine - Evan Hindoro; Arlis Karlina (Jurnal Kardiologi Indonesia, 2015)
A lot of hypertensive patients require two or more antihypertensive drugs to control and maintain normal blood pressure. Combination of antihypertension is recommended either as first or second line treatment. Among available antihypertension medications, combination of renin-angiotensinaldosteron (RAAS) inhibitor with calcium channel blocker or diuretics are more recommended as they have sinergistic clinical and biomolecular effects.Furthermore, single pill dosage is associated with higher patients compliants and lower faults incidence in medication. Severeal fixed-dose combinations are currently available in the market to give easier hypertension control and patients compliants. This short review focus on combination of perindropril and amlodipine